2021
DOI: 10.48550/arxiv.2104.03327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interacting galaxies in the IllustrisTNG simulations -- III: (the rarity of) quenching in post-merger galaxies

Salvatore Quai,
Maan H. Hani,
Sara L. Ellison
et al.

Abstract: Galaxy mergers are traditionally one of the favoured mechanisms for the transformation of spiral galaxies to spheroids and for quenching star formation. To test this paradigm in the context of modern cosmological simulations, we use the IllustrisTNG simulation to investigate the impact of individual merger events on quenching star formation (i.e. star formation rate at least 3𝜎 below the star-forming main sequence) within 500 Myr after the coalescence phase. The rate of quenching amongst recently merged galax… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…It was indeed shown that it is the only mode able to expel gas away from the centre of galaxies (Weinberger et al 2018;Terrazas et al 2020;Quai et al 2021) thanks to the release of mechanical energy into the gas (via winds in random directions). On the other hand, as shown by Weinberger et al (2018), the AGN thermal injection mode does not efficiently couple with the gas in the galaxy environment, and thus it does not alter its spatial distribution (see also Terrazas et al 2020;Quai et al 2021). Of course, this thermal injection mode contributes to heating the gas in the inter-galactic medium in the filament.…”
Section: Analysis Of the Gas Depletion At R < R Intmentioning
confidence: 99%
“…It was indeed shown that it is the only mode able to expel gas away from the centre of galaxies (Weinberger et al 2018;Terrazas et al 2020;Quai et al 2021) thanks to the release of mechanical energy into the gas (via winds in random directions). On the other hand, as shown by Weinberger et al (2018), the AGN thermal injection mode does not efficiently couple with the gas in the galaxy environment, and thus it does not alter its spatial distribution (see also Terrazas et al 2020;Quai et al 2021). Of course, this thermal injection mode contributes to heating the gas in the inter-galactic medium in the filament.…”
Section: Analysis Of the Gas Depletion At R < R Intmentioning
confidence: 99%